Comparison of Patient Needs Following Two Hurricanes - Nufer, K. E (Academic emergency medicine, 2003)
OBJECTIVES: The New Mexico Disaster Medical Assistance Team (NMDMAT) has responded to more hurricanes than any other disaster. To asses if patient needs may be applied to future hurricanes, the patient needs after Hurricanes Andrew (HA) (FL, 8/92) and Iniki (HI) (HI, 9/92) were compared. The study question: did patient needs differ after these hurricanes? METHODS: Design: Retrospective review. Subjects: All patients seen by NMDMAT following HA and HI. Observations: Age, past medical history (PMH), chief complaint (CC), diagnosis, treatments, diagnostic tests, triage level (green/yellow/red) and disposition. Age was analyzed with Student's t-test, other data with chi-square. RESULTS: 1056 patients seen, 712 after HA and 344 after HI. Age did not differ. More patients had a PMH after HA (43.1% v 30.2% p <.001). There was no difference in the most common CCs of wounds, musculoskeletal pain (MSK), medication refill or rash. More patients had cold symptoms (URI) in HI (18.9% v 9.0% p <.001). The most common diagnoses of wounds, MSK, and cellulitis did not differ. URIs were diagnosed more often in HI (5.6% v 2.3%, p =.003). There was no difference in tetanus toxoid, antibiotics or analgesics given. Patients in HA had more diagnostic tests (29.5% v 2.3%, p <.0001). Patients had a higher acuity in HA (p <.0001). The proportion of patients sent to a hospital did not differ. CONCLUSION: Patient needs were similar after HA and HI and may be generalizable to future hurricanes. Only the proportion of URIs differed, which is insignificant when planning for disasters. Importantly, DMATs should be well stocked with wound care supplies, tetanus toxoid and analgesics when responding to hurricanes. The same proportion of patients required transport to a hospital despite a higher acuity level in HA, likely due to the increased availability and use of diagnostic tests. These results should be tested prospectively in a future hurricane.